A New Bibliographic Contribution. [Neli Gančeva. St. Clement of Ohrid]) - Иванова, Мая (Poznańskie Studia Slawistyczne, 2018)
This is a review of the most recent bibliography on St. Clement of Ohrid, which was prepared by Neli Gancheva, a philologist and bibliographer at the Cyrillo-Methodian Research Centre of the Bulgarian Academy of Science. This study, dedicated to the 1100 anniversary of St. Clement’s dormition, is a continuation of the previous Cyrillo-Methodian bibliographies (1934; 1942; 1980; 1983; 2003; 2010) and bibliographies on St. Clement (1966; 1980). It reflects 1302 publicationsof the last 35 years in the Bulgarian and foreign scholarship as well as popular papers and artistic works (both fine arts and music are included here as well); folklore texts about St. Clement and the scholarly research on the folklore material. In summary, the bibliographic work by Neli Gancheva comes on time, brings contributions and is extremely useful.